Diversity and Distribution of Odonata (Dragonflies and Damselflies) in the Fresh Water Swamp Lake Tasek Bera, Malaysia - Norma-Rashid, Y.; Sofian-Azirun, Mohd; Zakaria-Ismail, M. (2001)
Fifty-nine species of Odonata were collected in a recent Study in the freshwater swamp lake of Tasek Bera, Peninsular Malaysia, in contrast to 33 species that were recorded previously from the Ramsar site. This Study added 35 species to the odonate records and together with the museum records., the number of species for the site now stands at 78 from 12 families. The causal factors for the absence of 19 species and other biological aspects such as habitat clustering and temporal activity profile were discussed.